2013
DOI: 10.1177/0960327113506723
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of oxidative/nitrosative stress in mice with methionine–choline-deficient diet-induced nonalcoholic fatty liver disease

Abstract: Insulin resistance, oxidative stress, and proinflammatory cytokines play a key role in pathogenesis of nonalcoholic fatty liver disease (NAFLD). The aim of our study was to investigate the dynamics of oxidative/nitrosative stress in methionine–choline-deficient (MCD) diet -induced NAFLD in mice. Male C57BL/6 mice were divided into following groups: group 1: control group on standard diet; group 2: MCD diet for 2, 4, and 6 weeks (MCD2, MCD4, and MCD6, respectively). After treatment, liver and blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
4
21
0
5
Order By: Relevance
“…These results are in accordance with the previous reports suggested that SIL possess antioxidant, antiapoptotic, anti-inflammatory and immunomodulatory properties (Al-Rasheed et al, 2015Fraschini et al, 2002;Karimi et al, 2011;Pradeep et al, 2007). The hepatoprotective role of SIL was suggested to be due to its enhancement of CYP2E1 activity which has a major role in drug metabolism (Dejanovic et al, 2014;Jorgačević et al, 2014;Mahli et al, 2015;Wong et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in accordance with the previous reports suggested that SIL possess antioxidant, antiapoptotic, anti-inflammatory and immunomodulatory properties (Al-Rasheed et al, 2015Fraschini et al, 2002;Karimi et al, 2011;Pradeep et al, 2007). The hepatoprotective role of SIL was suggested to be due to its enhancement of CYP2E1 activity which has a major role in drug metabolism (Dejanovic et al, 2014;Jorgačević et al, 2014;Mahli et al, 2015;Wong et al, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the generation of ROS activates the stellate cells in the liver resulting in the deposition of extracellular matrix which contribute to the development of fibrosis or cirrhosis in the liver tissue. The current results also showed that NO was increased in the liver and kidney tissues which may be suggested by the role of ROS in the increase of the synthesis of inducible iNOS (isoform nitric oxide synthase) leading to the increase of the level of NO (Jorgačević et al, 2014).…”
Section: Discussionsupporting
confidence: 60%
“…MCD-diet led to an increased production of reactive oxygen species and at the same time decreased the activity of antioxidant enzymes (Jorgacevic et al, 2013;Luo et al, 2014). Free fatty acid incubation of HepG2 cells in vitro resulted in swollen mitochondria with increased inner matrix density and loss of cristae (Jun et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…These include obstructive sleep apnea-induced hypoxia [71,72], by-products of both carbohydrate [73][74][75][76][77] and lipid metabolism [78][79][80], and gut-derived bacterial toxins [81,82]. Furthermore, nonoxidative metabolites of ethanol [19,83,84], methanol/formaldehyde [27,85,86], and nitrosative stressors [87,88] may also contribute to NAFLD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%